Propuesta de mejora de calidad para el área de servicio del restaurante Zazu Quito - Ecuador - Pabón Valdiviezo, Lenin Marcelo (2017)
Objectives: To evaluate the effect of deep caries on root resorption in temporal molars in children aged 6 to 10 years attending the UDLA clinic in the period March - April 2017 and to compare through radiographs a healthy piece with a piece with pathology. Methods: The present investigation is an observational, analytical type. It consisted of children aged 6 to 10 years who attended the dental clinic of the UDLA, who complied with the inclusion and exclusion methods. It was evaluated whether the presence of caries enamel dentin (Deep) directly or not directly affects the root resorption process. Results: more than 95% of the pieces with caries had pathological reabsorption. Conclusions: Caries is associated with the process of reabsorption of temporal pieces, in most cases, it was expressed as a reduction in root lengths.